Examining the association between access to a primary care provider and perceived unmet mental health treatment need among New York City adults - Palak Oza; Rachelle Monteau; Wenhua Lu; Rachelle Monteau (Discover Public Health)
Abstract This study examined the relationship between having a primary care provider (PCP) and perceived unmet mental health treatment need in New York City (NYC) adults using data from the 2019 and 2020 NYC Community Health Survey. Logistic regression analysis was conducted to assess the independent association between having a PCP and perceived unmet mental health treatment need. In 2019, lacking a PCP significantly increased odds of perceived unmet mental health treatment need in unadjusted analysis, but not in adjusted analysis. Non-specific psychological distress (OR 8.63; 95% CI 5.51, 13.53; p < .001) and perceived unmet medical treatment need (OR 5.33; 95% CI 3.47; 8.20, p < .001) increased odds of perceived unmet mental health treatment need. Similar findings were observed in 2020. These findings suggest that integrating routine mental health screening in primary care and increasing access to quality medical care are important to reduce the mental health treatment gap in NYC adults.